2021
DOI: 10.1021/acs.jpclett.1c03095
|View full text |Cite
|
Sign up to set email alerts
|

A-Site Mixing to Adjust the Photovoltaic Performance of a Double-Cation Perovskite: It Is Not Always the Simple Way

Abstract: Considerable progress has been made in improving the performance of optoelectronic devices based on hybrid organic−inorganic perovskites of the form ABX 3 . However, the influences of A-site doping on the structure and dynamics of the inorganic perovskite crystal lattice and, in turn, on the optoelectronic performance of the resulting devices remain poorly understood at an atomic level. This work addresses this issue by combining the results of several experimental characterization methods for threedimensional… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 53 publications
0
4
0
Order By: Relevance
“…A‐site alloying hardly changes the energy levels of the valence band maximum (VBM) and conduction band minimum (CBM) because cations weakly interact with the octahedron matrix, thus contributing little to the orbit hybridization at the band edges. Even so, in Pb‐based perovskites, increasing the Cs content slightly raises the bandgap due to octahedral tilting, which influences the extent of the metal–halide orbital overlap 44 . In contrast, the undistorted cubic phase of Sn–Pb perovskites after Cs addition revealed that Cs causes only lattice contraction and no octahedral tilting, resulting in a minor electronic contribution at the band edges 45 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A‐site alloying hardly changes the energy levels of the valence band maximum (VBM) and conduction band minimum (CBM) because cations weakly interact with the octahedron matrix, thus contributing little to the orbit hybridization at the band edges. Even so, in Pb‐based perovskites, increasing the Cs content slightly raises the bandgap due to octahedral tilting, which influences the extent of the metal–halide orbital overlap 44 . In contrast, the undistorted cubic phase of Sn–Pb perovskites after Cs addition revealed that Cs causes only lattice contraction and no octahedral tilting, resulting in a minor electronic contribution at the band edges 45 .…”
Section: Resultsmentioning
confidence: 99%
“…Even so, in Pbbased perovskites, increasing the Cs content slightly raises the bandgap due to octahedral tilting, which influences the extent of the metal-halide orbital overlap. 44 In contrast, the undistorted cubic phase of Sn-Pb perovskites after Cs addition revealed that Cs causes only lattice contraction and no octahedral tilting, resulting in a minor electronic contribution at the band edges. 45 As a result, a small amount of Cs mixing (<12%) in A-sites has a negligible effect on the bandgaps of Sn-Pb mixed perovskites.…”
Section: Structural Optical and Compositional Analyses Of Thin Films ...mentioning
confidence: 96%
“…With respect to A-site doping, previous studies have demonstrated the successful replacement of Cs, FA or MA in APbX 3 perovskite crystals with some proportion of relatively larger cations, such as ethylammonium, [22,23] guanidinium, [24,25] dimethylammonium (DMA), [26,27] and methylene-diammonium. [28] The larger cations doping has been shown to improve both the optoelectronic properties and the stability significantly.…”
Section: Introductionmentioning
confidence: 99%
“…[30] The MA 1−x DMA x PbBr 3 (0 ≤ x ≤ 0.7) series of perovskite single crystals were prepared by Yao et al The results showed that low concentration of DMA doping significantly improved the photovoltaic performance. [27] This enhancement is mainly attributed to the change of the inorganic lattice structure caused by A-site doping, such as lattice parameters, relaxation of lattice strain, octahedral tilt oscillations and local changes in the rotational dynamics of octahedra in the lattice. [28,31,32] Despite the progress made in the above-mentioned areas, little is known about the effect of DMA doping on the structural properties of CsPbBr 3 perovskite, which limits the further development of hybrid perovskite materials with a wide range of functions.…”
Section: Introductionmentioning
confidence: 99%